A randomised controlled trial of perivenous tumescent anaesthesia in addition to general anaesthesia for surgical ligation and stripping of the great saphenous vein. (June 2020) - Nandhra, Sandip; Wallace, Tom; El-Sheikha, Joseph; Carradice, Daniel; Chetter, Ian
Introduction: Open surgical ligation and stripping of the great saphenous vein is a highly cost-effective treatment when compared with conservative management and foam sclerotherapy but has limitations including post-operative morbidity and pain. This study aims to identify if the addition of tumescent anaesthesia could improve patient outcomes following treatment. Methods: Patients with primary superficial venous incompetence undergoing open surgical ligation and stripping of the great saphenous vein were randomised to either General Anaesthesia (GA) alone (GA) procedure or the addition of tumescent (G + T). The primary outcome was bodily pain (within SF-36) at one week. Additional outcomes included post-procedural pain score (100 mm visual analogue scale), complications and quality of life. Results: A total of 90 patients were randomised for inclusion. There was no significant difference in primary outcome; bodily pain at one week. Secondary outcome of 4-h post-procedural scores were significantly lower in the G + T group (32 (20–54) mm vs. (GA alone) 56 (24–70) mm (P = 0.016)). Complications were minor and equivalent. Both groups saw a significant increase (worsening) in Aberdeen Varicose Vein Questionnaire scores at week 1 with the G + T group faring worse at six weeks (10.0 (Interquartile Range [IQR] 5.6–17.9) vs. 4.3 (IQR 2.7–7.9) P = 0.004). Conclusion: The G + T group did not demonstrate a significant difference in the one-week bodily pain domain. The addition of tumescent anaesthesia does improve immediate post-operative pain but appears to negatively impact on six-week quality of life. EudraCT Number: 2011-005574-39